Plant-based nanoemulsions with essential oils as edible coatings: A novel approach for strawberry preservation - Oliveira Filho, Josemar Gonçalves de [UNESP] (2022)
Objective: The aim of this study was to evaluate the potential of essential oils (EOs) as natural fungicides and their presence in bio-nanocomposite coatings based on arrowroot starch, carnauba wax nanoemulsion, and cellulose nanocrystals for application in quality maintenance and postharvest conservation of strawberries during storage. Methodology: The EOs of the species Green Mint (Mentha spicata), Peppermint (Mentha x piperita), Palmarosa (Cymbopogon martinii) and Howood (Cinnamomum camphora) were characterized by GC-MS and GC-FID, and the antifungal activity was evaluated by different methods in vitro, and in vivo against the main strawberry postharvest fungi. The effect of incorporating carnauba wax (0-15% by weight) using emulsion technology ─ micro- and nanoemulsion ─ on the characteristics (physical, technological and optical) of arrowroot starch films/coatings was investigated. After that, films/coatings were developed based on arrowroot starch with carnauba wax nanoemulsion, cellulose nanocrystals and essential oils of M. spicata and C. martinii were produced using the casting technique. The films were characterized for water barrier, tensile, thermal, optical and microstructure properties, as well as in vitro antifungal activity against Rhizopus stolonifer and Botrytis cinerea. Strawberries were coated with the developed coatings and were evaluated during storage (0, 3, 6, 9, and 12 days) for soluble solids content, pH, titratable acidity, mass loss, firmness, respiration rate, color, total fungi count and aerobic mesophilic bacteria counts, visual fungal deterioration, anthocyanin, ascorbic acid, and total phenols contents, and antioxidant activity. Results: The main components of essential oils were menthol (45.37%), menthone (20.13%), isomentone (16.94%), menthyl acetate (3.81%), pulegone (1.89%), α-terpinene (1.88%), isopulegol (1.83%), neoisomenthol (1.19%), and α-terpineol (1.08%) for essential oil of M. piperita, linalool (98.39 %) for essential oil of C. camphora and geraniol (83.82%), geranyl acetate (7.49%), linalool (2.48%) and caryophyllene (1.33%) for the essential oil of C. Martini. The greatest antifungal activity was promoted by M. spicata and C. martinii in the direct contact and steam contact methods, micro-well dilution and spore germination assay, and in vivo in the vapor phase in strawberries inoculated artificially with R. stolonifer and B. cinerea. The presence of carnauba wax in the films increased their hydrophobic characteristics, reducing water solubility, moisture, water vapor permeability and thermal stability, in addition to improving light barrier properties. Films with nanoemulsion showed lower permeability to water vapor and light barrier properties, as well as better tensile strength and smoother microstructure than films made with microemulsion. While the incorporation of cellulose nanocrystals decreased the moisture content and water vapor permeability of the films, the cellulose nanocrystals and essential oils decreased the transparency and affected the microstructure of the films. The incorporation of essential oils from M. spicata and C. martinii improved thermal stability and provided excellent activity against fungi that spoil the fruit. The films demonstrated an excellent barrier against mold growth, permeability to water vapor and UV/vis light. Coatings loaded with essential oils of M. spicata and C. martinii were able to sis, nificantly reduce the severity of B. cinerea and R. stolonifer in artificially inoculated strawberries. Bio-nanocomposite coatings improved the stability of strawberries during storage, minimizing mass loss, and changes in color, texture (except coatings with C. martinii essential oil), soluble solids, pH, titratable acidity, phenolic, anthocyanins, and ascorbic acid contents, and antioxidant activity compared to uncoated strawberries (control). Furthermore, coatings with essential oils from M. spicata and C. martinii showed antimicrobial activity, reducing visual deterioration by fungi and the counts of aerobic mesophilic bacteria and fungi and yeasts during storage. Conclusion: It can be concluded that bio-nancomposite coatings, mainly those loaded with M. spicata essential oil, can be used as antimicrobial coating materials to preserve fresh strawberries during post-harvest.